Airport operations - Ashford, Norman (McGraw Hill, 1997)
By far the most comprehensive book on the subject, the completely new Second Edition of Airport Operations updates the many developments in this fast-changing industry. The book provides a broad perspective on the effects of deregulation, privatization, and commercialization. Thoroughly illustrated, it examines the most current practices in airport security and terminal access, cargo relations, noise control, scheduling issues, and more. It is equally valuable to aviation educators and students as well as to airport personnel.